Using infrared thermography to study hydrostatic stress networks in granular materials - Jongchansitto P. (Royal Society of Chemistry, 2014)
The macroscopic mechanical behaviour of granular materials is governed bymicroscopic features at the particle scale. Photoelasticimetry is a powerful method for measuring shear stresses in particles made from birefringent materials. As a complementary method, we here identify the hydrostatic stress networks through thermoelastic stress analysis using infrared thermographic measurements. Experiments are performed on two-dimensional cohesionless monodisperse granular materials composed of about 1200 cylinders comprising two constitutive materials. We show that the experimental hydrostatic stress distributions follow statistical laws which are in agreement with simulations performed using molecular dynamics, except in one case exhibiting piecewise periodic stacking. Polydisperse cases are then processed. Themeasurement of hydrostatic stress networks using this technique opens new prospects for the analysis of granular materials.